1995
DOI: 10.1002/art.1780380512
|View full text |Cite
|
Sign up to set email alerts
|

Cd28 expression on t cell subsets in vivo and cd28‐mediated t cell response in vitro in patients with rheumatoid arthritis

Abstract: Objective. In view of the critical importance of the CD28-CD8O (B7/BB1) costimulatory pathway in antigen-specific T cell activation and clonal expansion, we examined CD28 surface molecule expression in vivo, and T cell receptodCD3-mediated and B7/BBlcostimulated T cell proliferation in vitro, in rheumatoid arthritis (RA).Methods. Two-color immunofluorescence analyses of peripheral blood and synovial fluid-derived T cells, as well as 3H-thymidine incorporation assays, were performed.Results. In the peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…In contrast, the expansion of CD28 Ϫ T cell subsets appears to be ligated to extraarticular sites of inflammation (32) and reflects a systemic antigen challenge, for example, persistent infection (58). Our findings parallel reports on CD8 ϩ T cells which show: (i) that CD8 ϩ CD28 high are enriched among the cells that migrate across endothelial monolayers (35) and (ii) that, in contrast to peripheral blood, RA synovial fluid T cells are almost exclusively CD28 ϩ (41), which lead us to independently suggest that CD28 high T cells may preferentially migrate to certain sites of inflammation (33,34,41).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, the expansion of CD28 Ϫ T cell subsets appears to be ligated to extraarticular sites of inflammation (32) and reflects a systemic antigen challenge, for example, persistent infection (58). Our findings parallel reports on CD8 ϩ T cells which show: (i) that CD8 ϩ CD28 high are enriched among the cells that migrate across endothelial monolayers (35) and (ii) that, in contrast to peripheral blood, RA synovial fluid T cells are almost exclusively CD28 ϩ (41), which lead us to independently suggest that CD28 high T cells may preferentially migrate to certain sites of inflammation (33,34,41).…”
supporting
confidence: 88%
“…In contrast, other studies of the PBL T cell proliferative response of active, untreated RA patients to TCR/CD3 ϩ CD28 costimulation show a similar response in RA patients and healthy controls (41). These previous studies did not, however, allow direct comparison of the proliferative capacity of T cells from active and inactive RA patients (28,29,41).…”
Section: Cd28 Levels In Cd4 T Cells From Ra Patients Correlate With Tmentioning
confidence: 81%
“…Indeed, the expression of CD28 on CD8 + T cells shows dramatic individual variation in humans, ranging from 18% to 87% of peripheral blood CD8 + T cells (30). In human transplant recipients, heterogeneity in the responsiveness to conventional immunosuppression is well recognized but poorly understood (31).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the studies using two-colour analysis by Alvarado et al [46], we demonstrated strictly that CD28 T cells are eliminated selectively in SLE. Sfikakis et al [47] suggested that the decrease of CD28 8 T cells in peripheral blood of rheumatoid arthritis (RA) patients might result from the migration of these cells to active sites of inflammation, from the comparative examination of both peripheral blood and synovial fluid T cells in RA patients. Although we cannot completely eliminate this possibility, it is unlikely that the migration of CD28 T cells is a common reason for T cell lymphopenia in SLE, since the homing of T cells to the specific organs is not typical except for certain cases.…”
Section: Discussionmentioning
confidence: 99%